The enhancement rate of immunity to rubella in pregnant women in Ahwaz city during 1988-98 - M Ghafourian Boroujerdnia (JRI, 2001)
Rubella is a viral and acute disease which can be observed in children and adults by symptoms such as lymphoid glands inflammation and dermatitis. Its public health importance is related to teratogenic effects of primary rubella in first trimester of pregnancy. Infection in this period of pregnancy causes various anomalies such as cataract, glaucoma, deafness, coronary-vascular disease, pneumonia, encephalitis, bone damage, blood disorders, interference with the function of endocrine glands and low weight birth. In order to compare the rate of immunity to rubella in pregnant women of Ahwaz city during 1988-98, 550 serum samples were collected and assessed for anti-rubella antibody by hemagglutination inhibition (HI) and ELIZA methods. The results showed that the immunity to rubella virus has been increased from 78% to 92% during this decade. Therefore with presence of high immunity of pregnant women to rubella virus, public vaccination against rubella is not recommended in Ahwaz city.
Keywords: Rubella, Pregnancy, Immunity, Vaccination, Congenital Rubella, Congenital anomaly